Sexual, bladder and bowel problems in people with spinal cord injury in rural KwaZulu-Natal, South Africa - Lauren Tomes; Sonti Pilusa (African Journal of Disability)
Background: Spinal cord injury (SCI) is a life-changing experience that comes with multiple health challenges such as bowel, bladder and sexual health problems. Studies on the experiences of people with SCI based in rural South Africa are scarce.